Interfaith Marriage and Qur’anic Interpretation in Southeast Asia: Reassessing al-‎Māʾidah (5):5 through Maqāṣid al-Sharīʿah - Saifullah Saifullah; Martha Eri Safira; raihanah raihanah (Universitas Islam Negeri Imam Bonjol Padang, 2026)
Studies on interfaith marriage in Muslim societies have generally focused either on Islamic ‎legal doctrine or on state regulation, while relatively little attention has been paid to how ‎Qur’anic interpretation is institutionalized within diverse socio-legal contexts. This article ‎examines the interpretation of al-Māʾidah (5):5 and its legal implications in Southeast Asia, ‎particularly in Indonesia, Malaysia, Brunei Darussalam, and Singapore. Employing a ‎qualitative library-based method, the study combines Qur’anic exegesis, maqāṣid al-sharīʿah, ‎and comparative family law analysis to investigate the interaction between scriptural ‎interpretation and legal regulation. The findings demonstrate that although classical exegetes ‎generally recognized the permissibility of marriage between Muslim men and women from ‎among the Ahl al-Kitāb, contemporary legal responses vary considerably across Southeast ‎Asia. These variations are shaped not only by exegetical reasoning but also by differences in ‎Muslim demographics, state-religion relations, legal pluralism, and national regulatory ‎frameworks. The study further proposes a transcendental-emancipatory reconciliatory ‎framework that integrates textual fidelity, maqāṣid-oriented reasoning, socio-legal pluralism, ‎and contextual interpretation to explain the coexistence of divergent legal approaches while ‎preserving the normative objectives of Islamic law. The article contributes to the growing ‎scholarship on Qur’anic interpretation and Islamic family law by demonstrating that the ‎contemporary meaning and application of al-Māʾidah (5):5 are significantly influenced by the ‎political, legal, and social realities of Southeast Asian Muslim societies.‎